IMPLEMENTASI KERJA SAMA MILITER INDONESIA DAN PRANCIS TERHADAP MODERNISASI ALUTSISTA INDONESIA PADA TAHUN 2015-2019 - Harahap, Aulia Rahmah; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to analyze the influence of the cooperation between Indonesia and France on the modernization of Indonesia's Main Weapon System Equipment (Alutsista) from 2015 to 2019. The modernization of Alutsista is crucial for Indonesia in maintaining national security and defense in the increasingly complex era of globalization. In order to fulfill the requirements for Alutsista, Indonesia has engaged in defense industry cooperation with France, which is considered more advanced in military technology. This research utilizes K. J. Holsti’s International Cooperation theory with Richard Bitzinger's Defense Transformation concept and employs a descriptive-analytical research method with a qualitative approach. The study adopts Neorealism perspective. Data were collected through a literature review from books, journals, reports, websites, and the analysis of official documents. The data analysis reveals that the cooperation between Indonesia and France in the field of Alutsista modernization has had positive impacts on Indonesia's technological advancements, expertise, and Alutsista capabilities. This cooperation involves technology transfer, personnel training, improvement of defense industry capabilities, and acquisition of advanced weapon systems. Although the resulting impacts are not immediate, the cooperation between Indonesia and France can be considered as contributing to the advancement of Indonesia's defense resources before achieving the Minimum Essential Force (MEF) in 2024. Keywords: Defense, Alutsista Modernization, MEF